2014
DOI: 10.1007/s11552-014-9695-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of Three Radiographic Views in Assessing for Scapholunate Instability

Abstract: Background Multiple wrist x-ray images have been described to assess for scapholunate (SL) instability. Some views may be redundant. The purpose of this study was to compare three plain x-ray views in identifying a traumatic diastasis of the SL interval. Methods Nineteen patients (19 wrists) with a positive scaphoid shift test and surgically confirmed SL ligament damage were identified. There were 15 males and 4 females with a mean age of 39 years. Pre-operative x-rays were reviewed, including posteroanterior … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 29 publications
(41 reference statements)
0
14
0
Order By: Relevance
“…Widening of the scapholunate >3 mm on the clenched fist view has been recognized as an indication of possible disruption of the scapholunate ligament. 14,18 In our sample of normal wrists, the clenching of the fist and radial and ulnar deviation show minimal change in the scaphoid and lunate position relative to one another (<2 mm). The normal scapholunate ligament maintains the position of the 2 bones throughout a full range in the coronal plane, as well as with clenching the fist.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Widening of the scapholunate >3 mm on the clenched fist view has been recognized as an indication of possible disruption of the scapholunate ligament. 14,18 In our sample of normal wrists, the clenching of the fist and radial and ulnar deviation show minimal change in the scaphoid and lunate position relative to one another (<2 mm). The normal scapholunate ligament maintains the position of the 2 bones throughout a full range in the coronal plane, as well as with clenching the fist.…”
Section: Discussionmentioning
confidence: 74%
“…2 The clenched fist view has previously been studied in scapholunate dissociation, and our goal was to assess the normal joint behavior in this position using dynamic CT imaging. 14,17,18 The advancements in CT scanning and software to utilize dynamic CT (4D CT) analysis have created a unique modality to examine the wrist. 4 Our goal was to establish a protocol for measurements of the normal joint, on a novel dynamic CT wrist scan.…”
Section: Introductionmentioning
confidence: 99%
“…4 In a further study by Patel et al, they compared multiple views including PA neutral, PA ulnar deviation, and PA clenched fist and showed that PA ulnar deviation and clenched fist were equal in detecting dynamic SLI. 7 Unfortunately, in that study, the method to perform the clenched fist view was not described.…”
Section: Discussionmentioning
confidence: 97%
“…Various dynamic tests have been described to improve the detection of scapholunate ligament injuries. 4,7,8 The clenched fist view has been an important addition to the armamentarium of X-ray views used to diagnose dynamic SLI. 8 The view accentuates the scapholunate gap secondary to the scapholunate ligament incompetence by driving the capitate proximally into the disrupted interval.…”
Section: Discussionmentioning
confidence: 99%
“…SL gap was measured on PA wrist radiographs in the midportion of the scaphoid and lunate. [11][12][13] All other angles were measured on true lateral wrist radiographs in 0 degrees of wrist extension by tracing the longitudinal axes of the appropriate carpal bones. 14,15 The scaphoid axis was represented by a tangential line connecting the palmar convexities of the proximal and distal poles.…”
Section: Methodsmentioning
confidence: 99%